Moscow International Forum of Art Initiatives '98. : Senses Test Station. - Alpatova, Irina; Bochenkova, Irina; Jaseviciute, Violetta; Mogilevskaya, Tatyana; Nikich, Georgy; Sarkisyan, Oksana; Soans, Hanno (Moscow : International Forum of Art initiatives, 1998)
Antinis, Robertas ; Andriuskevicius, Aleksas ; Bartulus, Vidmantas ; Kasinskas, Virginijus ; Slapikas, Algimantas ; Ovchinnikov, Nikolai ; Shutov, Sergey ; Grantseva, Arina ; Egorova, Olga ; Pershina-Yakimanskaya, Natalia ; Kirtsova, Alyona ; Agroskin, Semyon ; Antoshina, Tanya ; Beliayev-Gintovt, Alexei ; Kamenetskaya, Natalia ; Salakhova, Aidan ; Vaisanan, Hanny ; Zatulovskaya, Irina ; Rees, Adriaan ; Heiskonen, Outi ; Kurvitz, Raoul ; Mikk, Toomas ; Raus, Urmo ; Saag, Sven ; Soans, Jaak ; Toomik, Jaan ; Braila, Pavel ; Dragnev, Lilia ; Macari, Lucia ; Druta, Veaceslav ; Rata, Vasile ; Mazurov, Vyacheslav ; Pogarsky, Michael ; Spirina, Elena ; Strelkov, Eugene ; Tishkov, Leonid ; Khotenov, Yury ; Levashov), Lefv (Vladislav Efimov - Vladimir ; Boonpuknwig, Navajul ; Chang, Fei Hsia ; Claude, Magali ; Shaawanasia, Michael ; Müller, Claudia & Julia ; Poyo, Txuspo ; Tan, Fiona ; Toomey, Rachel
Moscow International Forum of Art Initiatives 1998
Engels & Russisch
boek